Factors Affecting the Development of Anxiety in Postmenopausal Women: A CrossSectional Study in Coastal Areas: FaktorFaktor yang Mempengaruhi Terjadinya Kecemasan pada Perempuan Pascamenopause: Suatu Studi Potong Lintang di Daerah Pesisir - Juminten Saimin; Satrio Wicaksono; Junuda Junuda; Minarti Minarti (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To analyze factors associated with anxiety in postmenopausal women. Methods: This study was descriptive analytic with cross-sectional approach conducted in 228 postmenopausal women that aged 50-64 years old in coastal areas of Kendari City. Samples were taken by simple random sampling. The technique of collecting data used questionnaires and the Taylor Manifest Anxiety Scale (T-MAS). Data were analyzed using Chi-square test with a significance value p ï‚£ 0.05. Results: The results showed that 188 respondents (82.4%) had. anxiety. Its most experienced anxiety was aged 50-54 years old (37.7%), low education (96.0%), as housewife (62.7%), low income (91.2%) and lived with a partner (54.4%). There was correlation between anxiety with age (p=0.016), education level (p = 0.009), income (p = 0.011), and residence status (p = 0.029). There was no correlation between anxiety with occupation (p = 0.351). Conclusion: There was a correlation between anxiety in postmenopausal women in coastal areas with age, education level, income, and residence status. Keywords: age, anxiety, education level, income, postmenopausal women, residence status